Odpowiedzi

Najlepsza Odpowiedź!
2010-03-11T19:49:19+01:00
A) 3b+(b+1)=3b+b+1=4b+1
b) 5a-(a+1)=5a-a+1=4a+1
c) 2x-(3-5-x)=2x-3+5+x=3x+2
d) 2a+(3a-2b)+(a+b)=2a+3a-2b+a+b=6a-b
e) 5a-(2-x)+b-2x+5=5a-2+x+b-2x+5=5a+3-x+b
f) 7k-(m-2n+k)-(5k-3)+(2k-1)= 7k-m+2n-k-5k+3+2k-1=3k-m+2n+2
2010-03-11T19:50:05+01:00
A) 3b+(b+1)=3b+b+1=4b+1
b) 5a-(a+1)=5a-a-1=4a-1
c) 2x-(3-5-x)=2x-3+5+x=2x+x-3+5=3x+2
d) 2a+(3a-2b)+(a+b)=2a+3a-2b+a+b=2a+3a+a-2b+b=6a-b
e) 5a-(2-x)+b-2x+5=5a-2+x+b-2x+5=5a+b+x-2x-2+5=5a+b-x+3
f) 7k-(m-2n+k)-(5k-3)+(2k-1)=7k-m+2n-k-5k+3+2k-1=
=7k-k-5k+2k-m+2n+3-1=3k-m+2n+2
2010-03-11T19:56:37+01:00
A) 3b+(b+1)=3b+b+1=4b+1
b) 5a-(a+1)=5a-a+1=4a+1
c) 2x-(3-5-x)=2x-3+5+x=3x+2
d) 2a+(3a-2b)+(a+b)=2a+3a-2b+a+b=6a-b
e) 5a-(2-x)+b-2x+5=5a-2+x+b-2x+5=5a+3-x+b
f) 7k-(m-2n+k)-(5k-3)+(2k-1)= 7k-m+2n-k-5k+3+2k-1=3k-m+2n+2